Phytochemical Analysis and Cytotoxic Activity of Hexane Extract from Lasiosphaera nipponica - Manoharan Karuppiah Pillai (Fine Chemical Engineering, 2022)
Lasiosphaera nipponica finds therapeutic applications as a hemostatic in the traditional Japanese and Chinese medicines. The present study aimed to analyse the phytochemical compositions of two fractions from a hexane extract of L. nipponica by GC-MS analysis and evaluate the cytotoxic activity of these two fractions and a pure compound viz. ergosterol peroxide by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT assay). A hexane extract from L. nipponica was obtained by maceration technique and silica gel column chromatography of this hexane extract led to obtain two fractions and three pure compounds. The two fractions were analysed for phytochemical compositions by GC-MS and the presence of fatty acids, esters of fatty acids and ethyl 9-oxononanoate were identified. Additionally, these two fractions were evaluated for cytotoxic activity in P388, HL60, MCF7, HepG2 and J82 cancer cell lines in culture by MTT assay. Fraction 1 showed good activity in P388 and HL60 cancer cell lines with IC50 values of 9.8 and 18.2 μg/mL, respectively. Fraction 2 also showed good activity in P388 and HL60 cancer cell lines with IC50 values of 19.4 and 16.2 μg/mL, respectively. However, these two fractions did not show any appreciable activity in MCF7, HepG2 and J82 cancer cell lines. The three pure compounds were characterised as n-hexadecanoic acid, n-octadecanoic acid and ergosterol peroxide by spectroscopic means. Of these three pure compounds, only ergosterol peroxide was evaluated for cytotoxic activity in HL60, HepG2 and J82 cancer cell lines. Ergosterol peroxide showed an IC50 value of 82.2 μM (35.1 μg/mL) in HL60 cancer cell lines but it did not show any appreciable activity in HepG2 and J82 cancer cell lines. n-Hexadecanoic acid and n-octadecanoic acid were not evaluated for cytotoxic activity since they obtained in small quantity. From this study, we concluded that the fractions from a hexane extract of L. nipponica have therapeutically important phytochemicals and they exhibited promising cytotoxic activity in P388 and HL60 cancer cell lines. Further studies on L. nipponica are required to explore its therapeutic applications.